Hubungan Pengetahuan dan Penggunaan Kosmetik dengan Kejadian Acne Vulgaris Pada Remaja Putri di SMAN 7 Kota Jambi - Patriani, Sirly; Jayanti, Ova; Sulistiawati, Ira (Jurnal Akademika Baiturrahim Jambi, 2025)
Acne vulgaris is a chronic inflammatory disease of the pilosebaseus unit accompanied by blockage of the keratin duct gland material characterized by the presence of blackheads, papules, pustules, nodules, cysts are often found also scars in predilection areas such as face, upper shoulder of the superior extremities, chest and back that often occur in adolescence. The disease is not fatal, but it is quite worrying because it is associated with lowering confidence due to reduced facial beauty of the sufferer. Based on research in Southeast Asia, there are 40-80% of cases based on the Indonesian Cosmetic Dermatology Study Group PERDOSKI (2017) in Indonesia Acne vulgaris ranked third in the third most number of visitors to the Department of Skin and Sex Health Sciences in hospitals and skin clinics. Every year, there is an increase in acne sufferers. The purpose of this study was to find out the relationship of Knowledge and the merit of acne vulgaris in teenage girls in SMAN 7 Jambi City. This method of research is quantitative research with Descriptive analytics research design with cross sectional approach. The subject of this study is Teen Princess in SMAN 07 Jambi City which meets inclusion criteria and is willing to be respondents, this research sample is Teen Princess totaling 30 people who are in SMAN 07 Jambi City. The sampling technique is done with proposional random sampling. The research was conducted in September 2024 until August 2025. This research instrument uses questionnaires containing structured questions, data collection in this study using structured interview methods. The analysis used is bivariate analysis, the statistical size is displayed in the form of frequency distribution and percentage. The results of the analysis show the value of PR = 1.029 (95% CI: 0.597–1.773) with p-value = 0.042, meaning there is a significant link between the level of knowledge and the incidence of acne vulgaris.